2014
DOI: 10.1111/jonm.12260
|View full text |Cite
|
Sign up to set email alerts
|

The impact of organisational factors on horizontal bullying and turnover intentions in the nursing workplace

Abstract: The results suggest that reforming flawed organisational processes that contribute to registered nurses' bullying experiences may help to reduce chronically high turnover. Nurse leaders and managers need to create workplace processes that foster positive networks, fairness and respect through more transparent and accountable practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
86
1
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(94 citation statements)
references
References 30 publications
1
86
1
6
Order By: Relevance
“…This speaks to the protective nature of psychological safety in reducing the risk of work disengagement among nurse bystanders to bullying. These findings are in line with previous research that has suggested an association between nurse bullying and intention to leave (Blackstock et al., ; Johnson & Rea, ; Wilson et al., ). However, those studies did not distinguish between direct experience and witnessing of bullying as factors associated with intention to leave.…”
Section: Discussionsupporting
confidence: 92%
“…This speaks to the protective nature of psychological safety in reducing the risk of work disengagement among nurse bystanders to bullying. These findings are in line with previous research that has suggested an association between nurse bullying and intention to leave (Blackstock et al., ; Johnson & Rea, ; Wilson et al., ). However, those studies did not distinguish between direct experience and witnessing of bullying as factors associated with intention to leave.…”
Section: Discussionsupporting
confidence: 92%
“…In Brazil, turnover has been used as an important indicator of the quality of hospital management (PROAHSA, ). A positive association between bullying and TI among nurses has been evidenced in studies conducted in China (Lee et al, ; Tsai et al, ), Korea (Hyun‐Jung & Dahye, ) and Canada (Blackstock, Harlos, Macleod, & Hardy, ). Therefore, the first hypothesis of this study is that an increased perception of bullying is positively associated with increased TI among nurses.…”
Section: Introductionmentioning
confidence: 92%
“…The major themes of restrictive work practice, top down leadership, normalizing the abnormal in team dynamics and ethical concerns, have also been found internationally to be associated with increased RN turnover. [1,4,25,26] In this study, participants reported feeling unappreciated by their employer due to lack of commensurate benefits and pay, with many describing unfairness in the distribution patterns. Feeling unappreciated emanated from perception of lack of the professional development opportunities and poor remuneration.…”
Section: Discussionmentioning
confidence: 99%
“…[25,26] This lack of autonomy has been further linked to bullying in the workforce. [1] The RNs' lack of autonomy and the tendency towards autocratic leadership in these Kenyan private hospital based findings may be associated with the prevalence of bullying in the selected hospitals.…”
Section: Discussionmentioning
confidence: 99%